2018
DOI: 10.1097/jfn.0000000000000210
|View full text |Cite
|
Sign up to set email alerts
|

“It Had Only Been a Matter of Time Before I Had Relapsed Into Crime”: Aspects of Care and Personal Recovery in Forensic Mental Health

Abstract: By understanding the specific content along these themes, relevant to the individual patient, carers may be able to better support their personal recovery journey. Because time spent as inpatients in forensic psychiatry is an overarching issue, carers need to be persistent over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 17 publications
2
31
0
Order By: Relevance
“…The central factors supporting recovery as pointed towards by the informants in this study are in line with previous studies on recovery in forensic contexts [ 10 , 11 , 12 , 13 , 14 , 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The central factors supporting recovery as pointed towards by the informants in this study are in line with previous studies on recovery in forensic contexts [ 10 , 11 , 12 , 13 , 14 , 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…The central factors supporting recovery as pointed towards by the informants in this study are in line with previous studies on recovery in forensic contexts [10][11][12][13][14][15][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, a recent qualitative study of FMH service users' own views on reducing their risk of serious offending found that the emerging themes fit into personal recovery processes described for general psychiatric populations. 14 Participants emphasised the importance of trust and creating a context with meaningful relations (connectedness), hope to reach a future goal (hope and optimism about the future) and being given the tools that they needed for their recovery (empowerment). Nevertheless, whether personal recovery processes for FMH service users are fully covered by the CHIME framework remains unclear.…”
mentioning
confidence: 99%
“…Patients can experience good care that leads to change and recovery or poor care that leads to no changes or worse outcomes. (10) Although HCPs in forensic psychiatric care can help patients reconcile their situation and alleviate their suffering, these outcomes can be undermined by the actions of colleagues, leading to a more alienated and asymmetric relationship with patients (11). Hörberg and Dahlberg (12) found that patients experience insecure care when their care is contingent on the level of satisfaction of the HCPs rather than of the patients, suggesting that forensic psychiatric care should be guided by input from patients rather than the HCPs, a focus that requires the organisation and the care culture to support caregivers in developing a more caring attitude towards their patients (13).…”
Section: Introductionmentioning
confidence: 99%